Public health practice and artificial intelligence: views of future professionals. - Mwase, Nandi S.; Patrick, Sean M.; Wolvaardt, Jacqueline; Van Wyk, Mari; Junger, Washington; Wichmann, Janine (Journal of Public Health: From Theory to Practice (2198-1833), 2025)
Background: Globally, artificial intelligence (AI) is expanding in healthcare and public health and AI education for students in these fields will be essential. It is therefore important that future public health professionals are aware of opportunities and challenges linked to AI. Aim: The aim of the study was to assess the perceptions and attitudes regarding AI among one such group of future public health professionals – Postgraduate Diploma in Public Health students – in South Africa. Methods: An online survey was sent to students enrolled for the Postgraduate Diploma in Public Health programme from 13 June 2022 to 17 June 2022. Results: Six hundred and eighteen respondents completed an online survey (81.5% response rate). Generally, respondents thought AI would be capable of performing various tasks that did not provide direct care to individuals. Most (69%) agreed that introduction of AI could reduce job availability in public health fields. Respondents agreed that AI in public health could raise ethical (84%), social (77%) and health equity (77%) challenges. Relatively few respondents (52%) thought they were being adequately trained to work alongside AI tools, and the majority (76%) felt training of AI competencies should begin at an undergraduate level. Conclusion: Respondents expect AI to eventually carry out specific functions in public health and had reservations that AI may cause ethical challenges and increase unemployment in the country. Further exploration is needed regarding the perceptions about AI and its integration into the health system and the implications for undergraduate and postgraduate curricula.